Experimental and Theoretical Analysis for Hypoeutectic Cast Iron Oxidation Behaviors. Issue 4 (1st April 2023) - Sun, Chenteng; Wang, Qiaoling; Tao, Wen; Li, Aqiao; Xu, Qian; Li, Ying; Li, Shenggang; Zou, Xingli; Cheng, Hongwei; Lu, Xionggang
Abstract : The anodic dissolution of hypoeutectic cast iron consisting of pearlite and ledeburite was studied in the sulfuric acid solution by electrochemical methods. The oxidation activities of ferrite and cementite, which are two phases in cast iron, are evaluated by their structural and electronic properties according to the first-principles calculations. The results show that the anodic dissolution of ferrite occurs at the more negative potential compared with cementite. With comparison of ledeburite, the microstructure of pearlite is easier to be crumbled during the anodic dissolution because more amount of ferrite dissolves from the framework of pearlite. The first principle calculations demonstrate the Fe 3d-band center of iron is closer to Fermi level than that of cementite, indicating that Fe atoms in ferrite are more active and prone to suffering electrophilic attack. It is the intrinsic reason that cementite is more stable than ferrite under anodic polarization in the sulfuric acid solution.